Accountability of the Implementation of CPNS Recruitment in the Regional Personnel Agency of North Maluku Province in 2019 - Karjo Nalu; Irsan Makaminang (Peneliti.net, 2021)
Improvement of the CPNS acceptance system using CAT is part of increasing accountability in personnel recruitment state civil. This system applies throughout Indonesia, including North Maluku. With this system, the space misuse of power and authority (abuse of power) level public officials in North Maluku provincial government environments can be controlled as best as possible. This study is intended to answer the process to the impact of implementing accountability for CPNS recruitment in the regional personnel agency of North Maluku province. This research uses a qualitative method with a case study approach. The results of this study provide an illustration that the accountability of the implementation of CPNS recruitment at the Regional Personnel Agency of North Maluku Province using the Computer Assisted Test has a very accountable procedure so that it can be accepted by the community without carrying out resistance as the previous system (LJK). With the Computer Assisted Test (CAT) system, it is possible to see the total value of the 2019 CPNS SKD test results immediately after the participants have finished taking the test, meaning that the accountability of CPNS recruitment in North Maluku Province is heading towards a better direction in answering the problem of collusion, corruption and nepotism (KKN).